Faktor Kondisi dan Hubungan Panjang Berat Ikan Duri (Hexanematichthys sagor) - Suprida Yani Nasution; Rusdi Machrizal (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the condition factors and the relationship between the length and weight of thorn fish in the waters of the Barumun River, Labuhanbatu, North Sumatra. The method used is the sampling method. The results showed that the total number of samples obtained during the study was 41 fish with a total length of thorn fish that was 20.8 cm - 25.1 cm and the average length of fish caught was 23.41 cm. Meanwhile, the weight of thorn fish is 72 g to 126 g, and the average fish weight is 106.2 g. In conclusion, the growth pattern of thorn fish in the Barumun Labuhanbatu River, North Sumatra, is a negative allometric. The condition factors in thorn fish indicate that the Barumun River environment supports the growth of thorn fish and has a balanced status. Keywords: Condition Factor, Hexanmatichthys sagor, Length Weight